p62 overexpression induces TDP-43 cytoplasmic mislocalisation, aggregation and cleavage and neuronal death - A. D. Foster (Nature Portfolio, 2021)
Abstract Amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD) that exist on a spectrum of neurodegenerative disease. A hallmark of pathology is cytoplasmic TDP-43 aggregates within neurons, observed in 97% of ALS cases and ~ 50% of FTLD cases. This mislocalisation from the nucleus into the cytoplasm and TDP-43 cleavage are associated with pathology, however, the drivers of these changes are unknown. p62 is invariably also present within these aggregates. We show that p62 overexpression causes TDP-43 mislocalisation into cytoplasmic aggregates, and aberrant TDP-43 cleavage that was dependent on both the PB1 and ubiquitin-associated (UBA) domains of p62. We further show that p62 overexpression induces neuron death. We found that stressors (proteasome inhibition and arsenic) increased p62 expression and that this shifted the nuclear:cytoplasmic TDP-43 ratio. Overall, our study suggests that environmental factors that increase p62 may thereby contribute to TDP-43 pathology in ALS and FTLD.